Metal base for solar street lamp and processing technology of metal base
By applying epoxy coatings combined with hyperbranched polysiloxane and modified carbon nanotube filler on the metal base of solar street lamps, the corrosion and aging of metal bases in extreme climates is solved, and higher weather resistance and hydrophobicity are achieved.
Patent Information
- Application Number
- CN202411796183.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
AI Technical Summary
The metal bases of existing solar street lamps are prone to corrosion and aging in extreme climates, resulting in reduced durability and reliability.
Using a processing process, epoxy ended polysiloxane is synthesized under a nitrogen environment and combined with hyperbranched polysiloxane and modified carbon nanotube filler to form an epoxy coating with excellent hydrophobic and corrosion-resistant properties, coated on the surface of the metal base.
It significantly improves the weather resistance and hydrophobicity of the metal base, extends its service life, and reduces damage caused by corrosion and aging.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal protection, in particular to a metal base for a solar street lamp and a processing technology thereof. Background Art
[0002] With the transformation of the global energy structure and technological progress, solar street lights, as a green and sustainable lighting solution, are gradually being widely used in urban and rural areas. As one of the core components of solar street lights, the metal base not only bears the functions of support and fixation, but also embodies multiple modern values in modern society. 1. Environmental friendliness. The metal base plays a role of support and stability in the solar street light system, but its environmental value cannot be ignored. Metal materials such as aluminum alloy and stainless steel have high recyclability and regeneration, which can reduce the negative impact on the environment during the manufacturing process. 2. Durability and reliability. Whether it is freezing in high-altitude areas or high salt fog environment in coastal areas, the metal base can provide reliable support to ensure the long-term stability and safety of the street light system. This durability and reliability not only reduces maintenance costs, but also extends the service life of street lights. 3. Safety and stability. The metal base has high structural stability and safety, and can withstand the impact of natural disasters such as wind and earthquakes. In areas where earthquakes occur frequently, the stability and seismic resistance of the metal base are particularly important, which can effectively prevent street lights from tipping over and being damaged.
[0003] However, solar street lights are usually exposed outdoors and face the influence of various climatic factors such as wind, sun, rain, snow and ice. Therefore, improving the weather resistance of the metal base can effectively extend its service life and reduce corrosion, aging and damage caused by environmental factors. Especially under extreme climatic conditions such as high cold, high temperature, high humidity, and high salt fog, the weather-resistant metal base can maintain stable physical and chemical properties to ensure the long-term reliable operation of the solar street light system. In addition, metal materials (such as aluminum alloy, stainless steel, etc.) are prone to corrosion in humid environments. Therefore, improving the hydrophobicity of the metal base can reduce the retention of moisture and salt, thereby reducing the corrosion rate and improving the durability and service life of the product.
[0004] In order to overcome the defects of the prior art, the present invention provides a metal base for a solar street lamp and a processing technology thereof. Summary of the invention
[0005] The object of the present invention is to provide a metal base for a solar street lamp and a processing technology thereof to solve the problems in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A processing technology for a metal base for a solar street lamp comprises the following steps:
[0008] Step 1: In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate are mixed, and the temperature is slowly raised to 50-55°C and stirred for reaction for 8-10 hours to obtain epoxy-terminated polysiloxane; NH2-POSS is dissolved in xylene, and then epoxy-terminated polysiloxane is added and ultrasonically dispersed uniformly, and the temperature is slowly raised to 100-110°C for reaction for 2-3 hours to obtain hyperbranched polysiloxane;
[0009] Step 2: dissolving multi-walled carbon nanotubes in a mixture of deionized water and ethanol, and then slowly dropping concentrated ammonia water, ultrasonically dispersing for 60-80 minutes after the addition is completed, adding 0.10-0.15g / mL tetraethyl orthosilicate solution while ultrasonically dispersing, and continuing to stir and react for 20-25 hours after the ultrasonication is completed to obtain a silica colloidal solution; dissolving hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; adding the hydrolyzate to the silica colloidal solution, stirring and reacting for 10-13 hours, and after the reaction is completed, centrifuging, washing the precipitate, and vacuum drying to obtain a modified carbon nanotube filler;
[0010] Step 3: Mix the epoxy resin and xylene evenly, then add hyperbranched polysiloxane, modified carbon nanotube filler, dispersant, and leveling agent, add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 60-70°C for 30-40h to obtain the finished product.
[0011] More optimally, in step one, the preparation process of hydroxyl-terminated polysiloxane is as follows: in a nitrogen environment, octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, the temperature is raised to 90-100°C and stirred for 30-40 minutes, then the temperature is raised to 110-120°C and a catalyst and a capping agent are added, and the reaction is continued for 3-4 hours. After the reaction is completed, the temperature is raised to 150-160°C and the temperature is maintained for 1.5-2.0 hours, and then the hydroxyl-terminated polysiloxane is obtained by reducing the pressure and removing impurities.
[0012] More optimally, the contents of the components of the hydroxyl-terminated polysiloxane are: by mass, 24-28 parts of octamethylcyclotetrasiloxane, 50-60 parts of trifluoropropyltrimethylcyclotrisiloxane, 30-35 parts of tetramethyltetraenylcyclotetrasiloxane, 0.010-0.015 parts of catalyst, and 0.07-0.08 parts of end-capping agent; the catalyst is a tetramethylammonium hydroxide aqueous solution with a concentration of 25-30%; and the end-capping agent is H2O.
[0013] More optimally, in step 1, when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane to hydroxy-terminated polysiloxane is (1.0-1.3):2.
[0014] More optimally, in step 1, when preparing hyperbranched polysiloxane, the reaction molar ratio of the amino group in NH2-POSS and the epoxy group in the epoxy-terminated polysiloxane is 2:(4-5).
[0015] More optimally, the preparation process of NH2-POSS is as follows: dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly add 3-aminopropyltriethoxysilane, stir and react at 60-70°C for 20-25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:(55-60).
[0016] More optimally, in step 2, the volume ratio of deionized water to ethanol in the deionized water and ethanol mixture is 1:(3.0-3.5); the volume ratio of ethanol to acetic acid in the ethanol and acetic acid mixture is 1:(1.0-1.2).
[0017] More optimally, in step 2, the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:(0.04-0.05).
[0018] More optimally, in step three, the contents of the components of the epoxy coating are: by mass, 50-60 parts of epoxy resin, 25-30 parts of xylene, 10-12 parts of hyperbranched polysiloxane, 15-20 parts of modified carbon nanotube filler, 1-2 parts of dispersant, 1-2 parts of leveling agent, and 25-30 parts of polyamide 651 curing agent.
[0019] More optimally, in step three, the metal base is an aluminum alloy metal base, and the content of each element in the aluminum alloy metal base is: in mass fraction, 2.2-2.8% Si, 1.5-2.5% Cu, 1.1-1.6% Mg, 3.7-4.4% Zn, 0.6-1.2% Mn, 0.5-1% Fe, 0.4-0.8% Ni, 0.2-0.3% Cr, 0.15-0.25% Ti, 0.08-0.12% Ge, 0.04-0.07% Th, 0.03-0.05% Y, 0.02-0.03% Sm, 0.02-0.03% Tb, and the remainder is Al.
[0020] Beneficial effects of the present invention:
[0021] The present invention is characterized in that, in step one, hydroxyl-terminated polysiloxane is prepared by adding octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane as main raw materials. Further, by adding hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate, hydrolysis condensation reaction occurs, and finally epoxy-terminated polysiloxane is prepared. Epoxy-terminated polysiloxane is then added to NH2-POSS solution, a nucleophilic ring-opening reaction occurs, and epoxy-terminated polysiloxane with a large amount of fluorosilicon hydrophobic components is grafted to the surface of caged amino polysiloxane to obtain hyperbranched polysiloxane. In this step, the caged amino polysiloxane is used as the core, and silicon and fluorine hydrophobic structures with low surface energy are further grafted on the surface to obtain hyperbranched polysiloxane; on the one hand, the hyperbranched hydrophobic structure can effectively prevent the attachment of chemicals, microorganisms and other pollutants, so it has good corrosion resistance and surface cleaning ability. On the other hand, the large amount of silicon element introduced improves the UV resistance of the material. The siloxane group in the composite silicone can absorb and scatter ultraviolet rays, reduce the aging effect of ultraviolet rays on the material, and improve the weather resistance of the material, thereby ensuring that the product maintains stable performance in various harsh environments.
[0022] In addition, when preparing the hyperbranched polysiloxane, the reaction molar ratio of the amino group in NH2-POSS and the epoxy group in the epoxy-terminated polysiloxane is set to 2: (4-5), so a certain amount of epoxy groups will remain in the hyperbranched polysiloxane, so after adding the polyamide 651 curing agent in step three, the hyperbranched polysiloxane prepared by the present invention and the main resin epoxy resin will be fully compatible and undergo a chemical cross-linking reaction, and together with the main resin epoxy resin, a more stable cross-linking structure is formed, thereby optimizing the comprehensive performance of the material.
[0023] The present invention is characterized in that, in step 2, a carbon-silicon hybrid material is prepared by adding multi-walled carbon nanotubes and tetraethyl orthosilicate, and then hexadecyltrimethoxysilane is added to modify the carbon-silicon hybrid material to obtain a modified carbon nanotube filler. This step obtains a modified carbon nanotube filler with excellent hydrophobic corrosion resistance by introducing a hydrophobic long chain and a variety of reinforcing phases.
[0024] In step three, epoxy resin, xylene, hyperbranched polysiloxane, modified carbon nanotube filler, dispersant, leveling agent, and polyamide 651 curing agent are mixed to obtain epoxy coating; the epoxy coating is applied to the surface of the metal base and cured to obtain a finished product with good weather resistance and hydrophobicity. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Source of raw materials:
[0027] Multi-walled carbon nanotubes, provided by Nanjing Xianfeng Nanomaterials Technology Co., Ltd., with a diameter of 10nm; epoxy resin, provided by Tianjin Fengchuan Chemical Reagent Technology Co., Ltd., with industrial grade specifications; dispersant, provided by Shenzhen Longdi Chemical Co., Ltd., model BYK-2070; leveling agent, provided by BYK Chemical Technology Consulting Co., Ltd., specifically leveling agent BYD-354, with industrial grade specifications; polyamide 651 curing agent, provided by Beijing Xiangshan United Additive Factory, with industrial grade specifications; in terms of mass parts, one portion is 1g.
[0028] Example 1: Step 1: Under a nitrogen environment, 24g of octamethylcyclotetrasiloxane, 50g of trifluoropropyltrimethylcyclotrisiloxane and 30g of tetramethyltetraenylcyclotetrasiloxane were mixed, the temperature was raised to 100°C and stirred for 40min, then the temperature was raised to 120°C and 0.01g of catalyst and 0.07g of end-capping agent were added, and the reaction was continued for 4h. After the reaction was completed, the temperature was raised to 160°C and the temperature was kept for 2.0h, and then the hydroxyl-terminated polysiloxane was obtained by decompression and impurity removal; the catalyst was a 25% aqueous solution of tetramethylammonium hydroxide; the end-capping agent was H2O;
[0029] Dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 70°C for 25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57;
[0030] In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate were mixed, the temperature was slowly raised to 55°C and stirred for reaction for 10 hours to obtain epoxy-terminated polysiloxane; NH2-POSS was dissolved in xylene, and then epoxy-terminated polysiloxane was added and ultrasonically dispersed evenly, and the temperature was slowly raised to 110°C for reaction for 3 hours to obtain hyperbranched polysiloxane; when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane and hydroxyl-terminated polysiloxane was 1.1:2; when preparing hyperbranched polysiloxane, the reaction molar ratio of amino groups in NH2-POSS and epoxy groups in epoxy-terminated polysiloxane was 2:4.5;
[0031] Step 2: Dissolve multi-walled carbon nanotubes in a mixture of deionized water and ethanol, then slowly drop concentrated ammonia water, perform ultrasonic dispersion for 80 minutes after the addition is completed, add 0.1 g / mL tetraethyl orthosilicate solution while ultrasonic dispersion, continue stirring and reacting for 25 hours after the ultrasonication is completed to obtain a silica colloidal solution; dissolve hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; add the hydrolyzate to the silica colloidal solution, continue stirring and reacting for 13 hours, and after the reaction is completed, centrifuge, wash the precipitate, and vacuum dry to obtain a modified carbon nanotube filler; the volume ratio of deionized water and ethanol in the deionized water and ethanol mixture is 1:3; the volume ratio of ethanol and acetic acid in the ethanol and acetic acid mixture is 1:1; the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:0.05;
[0032] Step 3: Mix 50g of epoxy resin and 25g of xylene evenly, then add 10g of hyperbranched polysiloxane, 15g of modified carbon nanotube filler, 1g of dispersant, and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 70°C for 40h to obtain the finished product.
[0033] Example 2: Step 1: Under a nitrogen environment, 24 g of octamethylcyclotetrasiloxane, 50 g of trifluoropropyltrimethylcyclotrisiloxane and 30 g of tetramethyltetraenylcyclotetrasiloxane were mixed, heated to 95°C and stirred for 35 min, then heated to 115°C and added with 0.01 g of catalyst and 0.07 g of end-capping agent, and the reaction was continued for 3.5 h. After the reaction was completed, the temperature was raised to 155°C and kept warm for 1.7 h, and then reduced pressure was removed to obtain a hydroxyl-terminated polysiloxane; the catalyst was a 25% aqueous solution of tetramethylammonium hydroxide; the end-capping agent was H2O;
[0034] Dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 65°C for 23 hours, cool to room temperature after the reaction, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57;
[0035] In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate were mixed, the temperature was slowly raised to 53°C and stirred for reaction for 9 hours to obtain epoxy-terminated polysiloxane; NH2-POSS was dissolved in xylene, and then epoxy-terminated polysiloxane was added and ultrasonically dispersed evenly, the temperature was slowly raised to 105°C and reacted for 2.5 hours to obtain hyperbranched polysiloxane; when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane and hydroxyl-terminated polysiloxane was 1.1:2; when preparing hyperbranched polysiloxane, the reaction molar ratio of amino groups in NH2-POSS and epoxy groups in epoxy-terminated polysiloxane was 2:4.5;
[0036] Step 2: Dissolve multi-walled carbon nanotubes in a mixture of deionized water and ethanol, then slowly drop concentrated ammonia water, perform ultrasonic dispersion for 70 minutes after the addition is completed, add 0.1 g / mL tetraethyl orthosilicate solution while ultrasonic dispersion, continue stirring and reacting for 23 hours after the ultrasonication is completed to obtain a silica colloidal solution; dissolve hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; add the hydrolyzate to the silica colloidal solution, continue stirring and reacting for 11 hours, and after the reaction is completed, centrifuge, wash the precipitate, and vacuum dry to obtain a modified carbon nanotube filler; the volume ratio of deionized water and ethanol in the deionized water and ethanol mixture is 1:3; the volume ratio of ethanol and acetic acid in the ethanol and acetic acid mixture is 1:1; the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:0.05;
[0037] Step 3: Mix 50g of epoxy resin and 25g of xylene evenly, then add 10g of hyperbranched polysiloxane, 15g of modified carbon nanotube filler, 1g of dispersant, and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 65°C for 35h to obtain the finished product.
[0038] Example 3: Step 1: Under a nitrogen environment, 24g of octamethylcyclotetrasiloxane, 50g of trifluoropropyltrimethylcyclotrisiloxane and 30g of tetramethyltetraenylcyclotetrasiloxane were mixed, the temperature was raised to 90°C and stirred for 30min, then the temperature was raised to 110°C and 0.01g of catalyst and 0.07g of end-capping agent were added, and the reaction was continued for 3h. After the reaction was completed, the temperature was raised to 150°C and the temperature was kept for 1.5h, and then the hydroxyl-terminated polysiloxane was obtained by decompression and impurity removal; the catalyst was a 25% aqueous solution of tetramethylammonium hydroxide; the end-capping agent was H2O;
[0039] Dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 60°C for 20 hours, cool at room temperature after the reaction, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57;
[0040] In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate were mixed, the temperature was slowly raised to 50°C and stirred for reaction for 8 hours to obtain epoxy-terminated polysiloxane; NH2-POSS was dissolved in xylene, and then epoxy-terminated polysiloxane was added and ultrasonically dispersed evenly, the temperature was slowly raised to 100°C and reacted for 2 hours to obtain hyperbranched polysiloxane; when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane and hydroxyl-terminated polysiloxane was 1.1:2; when preparing hyperbranched polysiloxane, the reaction molar ratio of amino groups in NH2-POSS and epoxy groups in epoxy-terminated polysiloxane was 2:4.5;
[0041] Step 2: dissolve multi-walled carbon nanotubes in a mixture of deionized water and ethanol, then slowly drop concentrated ammonia water, perform ultrasonic dispersion for 60 minutes after the addition is completed, add 0.1 g / mL tetraethyl orthosilicate solution while ultrasonic dispersion, continue stirring and reacting for 20 hours after the ultrasonication is completed to obtain a silica colloidal solution; dissolve hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; add the hydrolyzate to the silica colloidal solution, continue stirring and reacting for 10 hours, and after the reaction is completed, centrifuge, wash the precipitate, and vacuum dry to obtain a modified carbon nanotube filler; the volume ratio of deionized water and ethanol in the deionized water and ethanol mixture is 1:3; the volume ratio of ethanol and acetic acid in the ethanol and acetic acid mixture is 1:1; the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:0.05;
[0042] Step 3: Mix 50g of epoxy resin and 25g of xylene evenly, then add 10g of hyperbranched polysiloxane, 15g of modified carbon nanotube filler, 1g of dispersant, and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 60°C for 30h to obtain the finished product.
[0043] Comparative Example 1: Step 1: Preparation of hyperbranched polysiloxane is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Dissolve multi-walled carbon nanotubes in a mixture of deionized water and ethanol, and then slowly drop concentrated ammonia water, and ultrasonically disperse for 80 minutes after the addition is completed, and add 0.1g / mL tetraethyl orthosilicate solution while ultrasonically dispersing. After the end of the ultrasound, continue to stir and react for 25 hours to obtain a silica colloidal solution; dissolve hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; add the hydrolyzate to the silica colloidal solution, continue to stir and react for 13 hours, and after the reaction is completed, centrifuge, wash the precipitate, and vacuum dry to obtain a modified carbon nanotube filler; the volume ratio of deionized water and ethanol in the deionized water and ethanol mixture is 1:3; the volume ratio of ethanol and acetic acid in the ethanol and acetic acid mixture is 1:1; the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:0.05;
[0044] Step 2: Mix 50g of epoxy resin and 25g of xylene evenly, then add 15g of modified carbon nanotube filler, 1g of dispersant, and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 70°C for 40h to obtain the finished product.
[0045] Comparative Example 2: Step 2: Preparation of modified carbon nanotube filler is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Under a nitrogen environment, 24g of octamethylcyclotetrasiloxane, 50g of trifluoropropyltrimethylcyclotrisiloxane and 30g of tetramethyltetraenylcyclotetrasiloxane are mixed, the temperature is raised to 100°C and stirred for 40min, then the temperature is raised to 120°C and 0.01g of catalyst and 0.07g of end-capping agent are added, and the reaction is continued for 4h. After the reaction is completed, the temperature is raised to 160°C and the temperature is maintained for 2.0h, and then the hydroxyl-terminated polysiloxane is obtained by decompression and impurity removal; the catalyst is a 25% aqueous solution of tetramethylammonium hydroxide; the end-capping agent is H2O;
[0046] Dissolve tetraethylammonium hydroxide in a mixed solvent, then slowly drop 3-aminopropyltriethoxysilane, stir and react at 70°C for 25h, and after the reaction is completed, cool at room temperature, precipitate at low temperature, filter, and vacuum dry to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:57;
[0047] In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate were mixed, the temperature was slowly raised to 55°C and stirred for reaction for 10 hours to obtain epoxy-terminated polysiloxane; NH2-POSS was dissolved in xylene, and then epoxy-terminated polysiloxane was added and ultrasonically dispersed evenly, and the temperature was slowly raised to 110°C for reaction for 3 hours to obtain hyperbranched polysiloxane; when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane and hydroxyl-terminated polysiloxane was 1.1:2; when preparing hyperbranched polysiloxane, the reaction molar ratio of amino groups in NH2-POSS and epoxy groups in epoxy-terminated polysiloxane was 2:4.5;
[0048] Step 2: Mix 50g of epoxy resin and 25g of xylene evenly, then add 10g of hyperbranched polysiloxane, 1g of dispersant, and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 70°C for 40h to obtain the finished product.
[0049] Comparative Example 3: Remove step 1 and step 2, and the rest is the same as Example 1. The specific steps are as follows: Step 1: Mix 50g of epoxy resin and 25g of xylene evenly, then add 1g of dispersant and 1g of leveling agent, and add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 70°C for 40h to obtain the finished product.
[0050] Detection test:
[0051] Weather resistance test: The base of the solar street light needs to be able to withstand extreme weather conditions, such as high temperature, low temperature, ultraviolet radiation, wind and rain, etc. Therefore, the finished metal base prepared by the present invention should have good weather resistance to maintain its color and performance stability and prevent the coating from aging or falling off due to environmental factors. Therefore, the finished metal base prepared by the present invention is used as a sample, and the weather resistance of the sample is tested according to the ASTM G154 standard. The test time is 850 hours, and the surface of the sample is observed to judge the weather resistance of the sample.
[0052] Contact angle test: The metal base product prepared by the present invention is used as a sample, and the contact angle between the sample surface and water is measured using a contact angle tester of Guangdong Dainte Intelligent Technology Co., Ltd. to determine the hydrophobicity of the sample surface. The results are as follows:
[0053] UV aging resistance Contact angle / ° Example 1 No powdering, no discoloration 145 Example 2 No powdering, no discoloration 144 Example 3 No powdering, no discoloration 143 Comparative Example 1 The sample surface is powdered and discolored in many places 108 Comparative Example 2 Partial powdering and discoloration on the surface of the sample 125 Comparative Example 3 The surface of the sample is severely powdered and obviously discolored. 91
[0054] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. It can be seen from the experimental data that there is no obvious fluctuation in the various properties of the sample. Comparative Example 1: Remove step 1: the preparation of hyperbranched polysiloxane, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the UV aging resistance effect is powdering and discoloration in many places on the surface of the sample, and the contact angle is reduced to 108°. The reason for analysis is: the large amount of siloxane structure in the hyperbranched polysiloxane can effectively resist the erosion of environmental factors such as humidity and heat due to its excellent chemical stability, and at the same time significantly improves the hydrophobicity of the sample surface; therefore, after removing the preparation of hyperbranched polysiloxane, the weather resistance is reduced and the hydrophobicity is reduced.
[0055] Comparative Example 2: Step 2: Preparation of modified carbon nanotube filler is removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the UV aging resistance effect is partial powdering and discoloration on the surface of the sample, and the contact angle is reduced to 125°. The reason is analyzed as follows: the modified carbon nanotube filler contains hydrophobic long chains and a variety of reinforcing phases, so it has excellent hydrophobic corrosion resistance. Therefore, after the preparation of the modified carbon nanotube filler is removed, the weather resistance and hydrophobicity are reduced.
[0056] Comparative Example 3: Step 1 and Step 2 are removed, and the rest is the same as Example 1. It can be seen from the experimental data that, compared with Example 1, the UV aging resistance effect is that the surface of the sample is severely powdered and obviously discolored, and the contact angle is reduced to 91°. The reasons are analyzed as follows: hyperbranched polysiloxane and modified carbon nanotube fillers have a variety of hydrophobic structures and siloxane structures, so they have good hydrophobic properties and UV resistance. Therefore, after removing Step 1 and Step 2, the weather resistance and hydrophobicity are reduced.
[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0058] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for a metal base for a solar street lamp, characterized in that: The following steps are involved: Step 1: In a nitrogen environment, hydroxyl-terminated polysiloxane, γ-glycidyloxypropyltrimethoxysilane and catalyst stannous octoate are mixed, and the temperature is slowly raised to 50-55°C and stirred for reaction for 8-10 hours to obtain epoxy-terminated polysiloxane; NH2-POSS is dissolved in xylene, and then epoxy-terminated polysiloxane is added and ultrasonically dispersed uniformly, and the temperature is slowly raised to 100-110°C for reaction for 2-3 hours to obtain hyperbranched polysiloxane; Step 2: dissolving multi-walled carbon nanotubes in a mixture of deionized water and ethanol, and then slowly dropping concentrated ammonia water, ultrasonically dispersing for 60-80 minutes after the addition is completed, adding 0.10-0.15g / mL tetraethyl orthosilicate solution while ultrasonically dispersing, and continuing to stir and react for 20-25 hours after the ultrasonication is completed to obtain a silica colloidal solution; dissolving hexadecyltrimethoxysilane in a mixture of ethanol and acetic acid to obtain a hydrolyzate; adding the hydrolyzate to the silica colloidal solution, stirring and reacting for 10-13 hours, and after the reaction is completed, centrifuging, washing the precipitate, and vacuum drying to obtain a modified carbon nanotube filler; Step 3: Mix the epoxy resin and xylene evenly, then add hyperbranched polysiloxane, modified carbon nanotube filler, dispersant, and leveling agent, add polyamide 651 curing agent after sufficient ball milling to obtain epoxy coating; apply the epoxy coating to the surface of the metal base, and cure it at 60-70°C for 30-40h to obtain the finished product.
2. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step 1, the preparation process of hydroxyl-terminated polysiloxane is as follows: in a nitrogen environment, octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, the temperature is raised to 90-100°C and stirred for 30-40 minutes, then the temperature is raised to 110-120°C and a catalyst and a capping agent are added, and the reaction is continued for 3-4 hours. After the reaction is completed, the temperature is raised to 150-160°C and the temperature is maintained for 1.5-2.0 hours, and then the hydroxyl-terminated polysiloxane is obtained by decompression and impurity removal.
3. The processing technology of the metal base for solar street lamp according to claim 2 is characterized in that: The contents of the components of the hydroxyl-terminated polysiloxane are as follows: by mass: 24-28 parts of octamethylcyclotetrasiloxane, 50-60 parts of trifluoropropyltrimethylcyclotrisiloxane, 30-35 parts of tetramethyltetraenylcyclotetrasiloxane, 0.010-0.015 parts of a catalyst, and 0.07-0.08 parts of a capping agent; the catalyst is a tetramethylammonium hydroxide aqueous solution with a concentration of 25-30%; and the capping agent is H2O.
4. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step 1, when preparing epoxy-terminated polysiloxane, the reaction mass ratio of γ-glycidyloxypropyltrimethoxysilane to hydroxy-terminated polysiloxane is (1.0-1.3):
2.
5. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step 1, when preparing hyperbranched polysiloxane, the reaction molar ratio of the amino group in NH2-POSS and the epoxy group in the epoxy-terminated polysiloxane is 2:(4-5).
6. The processing technology of the metal base for solar street lamp according to claim 5 is characterized in that: The preparation process of NH2-POSS is as follows: dissolving tetraethylammonium hydroxide in a mixed solvent, then slowly adding 3-aminopropyltriethoxysilane, stirring and reacting at 60-70°C for 20-25h, cooling at room temperature after the reaction, precipitating at low temperature, filtering, and vacuum drying to obtain NH2-POSS; the mixed solvent includes deionized water, propanol, and acetonitrile in a volume ratio of 1:0.4:0.1; the reaction volume ratio of tetraethylammonium hydroxide and 3-aminopropyltriethoxysilane is 0.5:(55-60).
7. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step 2, the volume ratio of deionized water to ethanol in the deionized water and ethanol mixture is 1:(3.0-3.5); the volume ratio of ethanol to acetic acid in the ethanol and acetic acid mixture is 1:(1.0-1.2).
8. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step 2, the reaction mass ratio of multi-walled carbon nanotubes, tetraethyl orthosilicate, and hexadecyltrimethoxysilane is 0.5:2:(0.04-0.05).
9. The processing technology of the metal base for solar street lamp according to claim 1 is characterized in that: In step three, the contents of the components of the epoxy coating are: by mass, 50-60 parts of epoxy resin, 25-30 parts of xylene, 10-12 parts of hyperbranched polysiloxane, 15-20 parts of modified carbon nanotube filler, 1-2 parts of dispersant, 1-2 parts of leveling agent, and 25-30 parts of polyamide 651 curing agent.
10. The processing technology of the metal base for solar street lamp according to claim 1, characterized in that: In step three, the metal base is an aluminum alloy metal base, and the content of each element in the aluminum alloy metal base is: in mass fraction, 2.2-2.8% Si, 1.5-2.5% Cu, 1.1-1.6% Mg, 3.7-4.4% Zn, 0.6-1.2% Mn, 0.5-1% Fe, 0.4-0.8% Ni, 0.2-0.3% Cr, 0.15-0.25% Ti, 0.08-0.12% Ge, 0.04-0.07% Th, 0.03-0.05% Y, 0.02-0.03% Sm, 0.02-0.03% Tb, and the remainder is Al.